Nanotechnology Applications in Industry and Medicine - Ferreira, M. A. M.; Filipe, J.; Coelho, M.; José Chavaglia Neto (EasyChair Preprint Nº 7905, 2025)
Since some time ago, nanotechnology has become one of the most promising scientific hopes in several human domains. Countless scientific studies in several areas of knowledge have been made since the nanoscale emergence, bringing their contribution to the nanoscience development. The recent researches in this field allowed the union of interests from several areas, such as physical sciences, molecular engineering, biology, biotechnology and medicine for example, contributing to the investigation of Biosystems at a nanoscale. Nanotechnology and nanobiosystems are becoming a privileged domain in order to reach an advanced level in the human development in many fields, as: a) the biotechnology processes; b) the synthesis of new drugs and their delivery on a live bod; c) the regenerative medicine and the new technologies in medicine: biotechnology and nanotechnology, body area networks for telemedicine – nanomedicine, nanoimaging, nanotechnological implants, in-body diagnostic systems, nanobiomedical wired devices, etc. ;d) the application on the sustainability of the environment. Nanoscale can provide the tools to get better conditions to investigate Biosystems and to get advances with nanomaterials. These nanoscales, used in Biosystems, contribute to enhance very innovative and promising results in medical area. Improvements in the telemedicine and on health are expectable with new systems operations and new nanotechniques. Ethical, legal and social implications are posed and the need for discussing this theme shows the importance of nanotechnology to the society and the consequences, both positive and negative, that the development of nanotechnology will have to mankind in the future.